Diphenylsulfone-based hosts for electroluminescent devices: Effect of donor substituents - Bezvikonnyi, Oleksandr; Gudeika, Dalius; Volyniuk, Dmytro; Rutkis, Martins; Grazulevicius, Juozas V. (Elsevier Ltd, 2020)
In this work, we report on a series of diphenylsulfone derivatives substituted by 2-(trifluoromethyl)-phenothiazinyl, 10,11-dihydro-5H-dibenz[b,f]azepinyl, 5H-dibenz[b,f]azepinyl, 4-methoxy-carbazolyl and 1,2,3,4-tetrahydrocarbazolyl moieties. Utilization of such donating units provided high triplet levels (2.99–3.12 eV) of the designed compounds. The compounds were characterized by glass-forming properties (with glass transition temperatures of 68–162 °C) and ionization potentials of 5.61–5.99 eV. Depending on the donor substitution pattern, either hole or electron transport was observed for the studied compounds with charge mobilities in the range from 5.3 × 10−6 to 2.8 × 10−4 cm2/V at electric fields higher than 3.1·105 V/cm. Hosting properties of the compounds were studied using widely known emitter exhibiting thermally activated delayed fluorescence. Among the studied compounds, bis(4-(4-methoxy-9H-carbazole-9-yl)phenyl)sulfone showed the best performances in both guest:host solid films (photoluminescence quantum yield of 87%) and electroluminescent devices (maximum external quantum efficiency over 20%).
DG acknowledges to the ERDF PostDoc project No. 1.1.1.2/VIAA/1/16/177. This work was supported by the project of scientific co-operation program between Latvia, Lithuania and Taiwan ?Polymeric Emitters with Controllable Thermally Activated Delayed Fluorescence for Solution-processable OLEDs? (grant No. S-LLT-19-4). Support of the Lithuanian Academy of Sciences is gratefully acknowledged; Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART²
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Carbazole; Diphenylsulfone; Host; OLED; TADF